The mechanism of thiophene oxidation on metal-free two-dimensional hexagonal boron nitride. Issue 39 (25th September 2019) - Lv, Naixia; Sun, Linghao; Chen, Linlin; Li, Yujun; Zhang, Jinrui; Wu, Peiwen; Li, Hongping; Zhu, Wenshuai; Li, Huaming
Abstract : DFT calculations reveal the zigzag-N edge site is the most favorable site for thiophene oxidation, followed by the armchair and zigzag-B sites. Abstract : Hexagonal boron nitride (h-BN) as an outstanding catalyst has been applied in oxidative desulfurization (ODS). In order to increase its catalytic performance, deep insight into the catalytic mechanism is urgent. In this work, DFT calculations were carried out to explore thiophene oxidation on the h-BN surface sites, involving the perfect and zigzag B, zigzag N, and armchair edge sites, and B- or N-monovacancy site. The calculated results show that O2 is easily activated on defect sites such as the edge sites and N-vacancy sites. For the thiophene oxidation mechanism, our results show that the zigzag N edge site is the most favorable active site, followed by the armchair and zigzag B edge sites. For the vacancy sites, although they are active for O2 dissociation, the dissociated O is trapped in the vacancy site, and they are not active for eventual sulfone formation.